This train - Grady, James, 1949- (Simon & Schuster, 2022)
"This Train races us through America's heartland, carrying secrets. There is treasure in the cargo car, along with an invisible puppeteer. There is a coder named Nora, Mugzy, the yippy dog, and Ross, the too-curious poet. On board, it's a countdown to murder... On this train there is a silver madman, a targeted banker, and crises of conscience. This train harbors the "perfect" couple's conspiracies, the chaos of being a teenager, and parenthood alongside the wows of being nine. There is a widow and a wannabe, and the sleaziest billionaire. On this train, there is the suicide ticket, the bomb, sex, love, and loneliness. The heist. Revenge. Redemption. This Train is a ticking clock, roaring through forty-seven fictional hours of non-stop suspense and action, through the challenges of now: Racism. Sexism. Global warming. What it means to be alive. This train carries all of us. All aboard!" -- Jacket flap.